P.081 Using functional MRI to assess the applicability of surgery or radiosurgery for vascular malformations near eloquent cortex. (2nd June 2017) - Gould, L; Kelly, M; Ekstrand, C; Ellchuk, T; Borowsky, R; Mickleborough, M
Abstract : Background: Although surgery is the gold standard for treating brain arteriovenous malformations (AVMs), surgical techniques may not be suitable if the AVM is located in eloquent regions of the brain, such as the motor cortex. An alternative method for these cases is stereotactic radiosurgery. Localization of the motor cortex using functional magnetic resonance imaging (fMRI) is useful for helping the neurosurgeon determine which type of surgery is appropriate. We report a patient with a left frontal AVM near the motor cortex. fMRI was requested to localize motor functioning.Methods: The tasks included bilateral finger tapping, arm rubbing against the scanner, and abdominal tightening. All fMRI analyses were performed using BrainVoyager.Results: The fMRI results revealed that finger tapping and arm rubbing activated the precentral gyrus and supplementary motor area, and abdominal tightening activated the paracentral gyrus. These regions of activation were shown to be just posterior to the AVM and were mapped using neuronavigation during surgery.Conclusions: Given that the fMRI activation in the motor cortex was posterior to the AVM, the neurosurgeon felt confident that surgery could be performed. These findings elucidate the utility of fMRI for pre-surgical localization and for determining whether surgery or radiosurgery is appropriate in cases in which the AVM is near eloquent cortex.